Asymmetric Pectus Excavatum Is Associated with Overgrowth of Ribs Rather Than Cartilage - Park, Chul Hwan; Kim, Tae Hoon; Haam, Seok Jin; Lee, Sungsoo (The Thoracic and Cardiovascular Surgeon, 2015)
Background To evaluate whether the overgrowth of costal cartilage exists in patients with pectus excavatum, we compared the length of the costal cartilage and ribs between patients with asymmetric pectus excavatum and controls without chest wall deformity using three-dimensional computed tomography.Materials and Methods Nineteen adult patients with asymmetric pectus excavatum and 19 age and sex matched controls without chest wall deformity were enrolled. We measured the full lengths of the fourth to sixth ribs and costal cartilage using three-dimensional volume-rendered computed tomography images and curved multiplanar reformatting techniques. The lengths of ribs and costal cartilage, their summations, and the costal index ([length of cartilage/length of rib] × 100 [%]) were compared on the asymmetrically depressed side of patients (Group A), the opposite side of the same patients (Group B), and controls (Group C) at the fourth to sixth levels.Results The lengths of the ribs of groups A and B were significantly longer (p < 0.001) than those of group C (299.4 ± 14.9 mm vs. 302.9 ± 15.3 mm vs. 288.9 ± 12.2 at the fourth level, 312.3 ± 14.1 mm vs. 318.4 ± 14.6 mm vs. 303.2 ± 12.7 mm at the fifth level, and 322.2 ± 17.2 mm vs. 325.2 ± 17.5 mm vs. 309.4 ± 12.3 mm at the sixth level). The costal cartilage lengths did not differ (p > 0.05) among the three groups (53.1 ± 7.3 mm vs. 54.6 ± 8.6 mm vs. 52.9 ± 5.2 at the fourth level, 71.9 ± 9.6 mm vs. 72.3 ± 9.9 mm vs. 69.2 ± 7.1 mm at the fifth level, and 100.1 ± 15.2 mm vs. 104.2 ± 15.8 mm vs. 99.1 ± 9.1 mm at sixth level). The summations of the rib and costal cartilage lengths were longer in groups A and B than in group C. The costal indices were not different among the three groups at the fourth, fifth, and sixth rib levels.Conclusion In patients who had asymmetric pectus excavatum with a ≥ 21-degree angle of sternal rotations, the ribs but not the costal cartilage were longer than those of controls. These findings suggest that cartilage overgrowth is not the main factor responsible for asymmetric pectus excavatum, and it could instead be related to abnormal rib growth.
Keywords: pectus excavatum; costal cartilage; rib; three-dimensional computed tomography